Education and mortality in three Eastern European populations: findings from the PrivMort retrospective cohort study. (5th December 2018) - Doniec, Katarzyna; Stefler, Denes; Murphy, Michael; Gugushvili, Alexi; McKee, Martin; Marmot, Michael; Bobak, Martin; King, Lawrence
Abstract: Background: The aim of the study is 2-fold. Firstly, it attempts to investigate the potential impact of major political and economic changes on inequalities in all-cause mortality among men and women with different levels of education in three Eastern European countries. Secondly, to identify changes in contribution of smoking and drinking to educational differences in all-cause mortality. Study covers the period from 1982 to 2013. Methods: Data were collected in 2013–14 as a part of the PrivMort retrospective cohort study. Participants in Russia, Belarus and Hungary provided information on their educational attainment, health-related behaviors and vital statistics of their close relatives ( N = 179 691). Odds ratios for mortality and relative indices of inequality (RII) were estimated for individuals aged 20–65 years, stratifying by three levels of educational attainment: higher, secondary and less than secondary education. Results: Those in lower educational groups were significantly more likely to die, through most time periods and sub-groups. The RII increased over time in all countries and both genders, except for Hungarian men. Alcohol consumption and smoking have increasingly contributed to educational inequalities in mortality during this period. Conclusion: Educational inequalities in mortality in these Eastern European countries have increased during recent decades. Smoking and alcohol consumption, two major health-related behaviors, made a significant contribution to these increases in inequality.